Adj-Dicarbachlorin, the first free base carbaporphyrinoid system with an internal methylene unit. Issue 88 (17th September 2015) - Lash, Timothy D.; AbuSalim, Deyaa I.; Ferrence, Gregory M.
Abstract : Base-catalyzed condensation of dicyclopentadienylmethane with a dipyrrylmethane dialdehyde gave a dicarbachlorin with an internal CH2 group. Abstract : Base-catalyzed condensation of dicyclopentadienylmethane with a dipyrrylmethane dialdehyde gave a dicarbachlorin with an internal CH2 group. This unusual porphyrinoid retained highly diatropic characteristics and exhibited a porphyrin-like UV-vis spectrum.